Efektifitas dan Kepuasan Pengguaan Wireless Sebagai Media Ujian Berbasis Online (Study Kasus AMIK BSI Cikarang) - Feri Prasetyo Hidayat (Paradigma, 2013)
Wireless is one of the components the network connection on a computer network or interms of market called WiFi (wireless findelity) or hotspot. Of these research activities to find theextent of the efficient use of the WiFi network to test and exam UAS UTS College Academy At BSI,using conjoint analysis. This perception will be based on the results of each student use the wififacilities as a means of online exams, where the perception is based on data from several factorsderived from previous research include utilization factor, site access is used, satisfaction inNetworking. This study uses a correlation study between the Online Testing Applications withsatisfaction with the use of Wifi anlisis ConjointKey Word: Wifi, Online Test, Conjoint Analysis